SUBSTANTIATION THE PARAMETERS OF THE PRIMARY PROCESSING IN INSTALLATION BASED OF RENEWABLE ENERGY - Shavkat IMOMOV; Tulanboy KAYUMOV; Zulfiya MAMADALIEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this article there are described several mathematic analyses of load to energy installation during process of primary organic waste recycling. There is spoken about the positive influence to work effectiveness of biotechnological construction process of primary processing. Also, we can see some valuable information taken on the basis of the engineering research results for the construction of initial working out.